MORPHOLOGICAL AND KARYOLOGICAL STUDIES IN TWO WILD IRIS SPECIES (IRIDACEAE) OF TUNISIA - Hanen Ferjani; Faouzi Haouala; Messaoued Mars (European Scientific Journal, ESJ, 2015)
Morphological and cytological variation among two wild iris species (iris juncea (poir) and iris sisyrinchium. (l)) from tunisia was studied. Initially, morphological traits analyzed concern floral and vegetative characters. Analysis of variance showed significant differences. Higher variation coefficient belongs to flower height, flower diameter, filament length, seed diameter, and level number. Pearson coefficients correlations between different characters were positive and highly significant (p< 0.0001) for flower diameter and flower heigth. Factor analysis showed that only two axes define 100% of variance among characters. Secondly, in cytological variation each species had different karyotypic formula such as 2n = 32 = 30sm + 2st for iris juncea with a satellite in pair number 2; 2n= 24 = 18 st + 6 sm for iris sisyrinchium beja‘s population and 2n=26=18 st + 8sm for iris sisyrinchium hammamet population.